Delay adaptive transmission method for scalable video streaming based on OpenFlow - Tao HUANG; Li ZHANG; Yun-yong ZHANG; Yun-jie LIU (Tongxin xuebao)
For the current internet streaming media transmission delay sensitivity issues, a delay adaptive method for SVC (scalable video coding) streaming media transmission based on OpenFlow was proposed. This method combines SVC streaming scalable and flexible programmable features of OpenFlow effectively, and implements SVC streaming hierarchical adaptive transmission in a dynamic network,by building the base layer and the enhancement layer separate routes under complex network environment with limited network bandwidth and link congestion. Simulation results show that this method has an important role in improving efficiency and quality of the SVC streaming, so it can improve the user experience effectively.